Modelagem de processo crítico de manufatura utilizando linguagem de autômatos para liberação paramétricaq - Silva, João Gabriel Santos (2021)
The present work is focused on presenting an alternative to improve manufacturing processes using automata languages capable of enabling, through parametric release, the endorsement of products that were approved during quality tests and that did not present during their manufacture, any defective characteristics from the beginning until the last packaging station of the product so that it can be sold on the market. This study was based on a project carried out in a company from the Industrial Pole of Manaus during the internship period, in which quality criteria / standards were used to identify crucial stages of the production chain, in order to use concepts aimed at automaton languages capable of simulate an existing small-scale process. In order to allow fluid systems to control the advance to a stage to follow only in cases where a previous condition is met, a flow of execution of the equipment has been developed so that it is possible to perform the blocking of materials throughout any stage of its manufacture based on the analysis of conforming and non-conforming parameters in which its components / equipment if specified. Taking this alternative into consideration, it becomes feasible to propose a system capable of guaranteeing cost reduction with production losses, carrying out different simulations for events that may arise due to external interferences or from the equipment itself, mapping the states of each component during all its stages of the manufacturing process, in addition to increasing the reliability and safety of the finished product for the final consumer.